REKONSTRUKSI PERAN PENDIDIK BERBASIS TRILOGI KI HAJAR DEWANTARA DI ERA DIGITAL - Syauqi; Tasrid Syafa Muhammad; Mohammad Faizin (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2026)
The digital era has brought fundamental changes to the field of education, requiring Indonesian educators to rapidly adapt to technological advancements while simultaneously preserving humanistic values in the learning process. However, empirical realities indicate that teachers’ digital literacy remains relatively low, students’ character values are experiencing degradation, and disparities in technological adaptation persist. This study aims to analyze the challenges faced by Indonesian educators in the digital era and to examine the relevance of Ki Hajar Dewantara’s leadership trilogy as a conceptual framework for addressing these challenges. The research employs a qualitative method with a library research approach and content analysis of scholarly literature, policy documents, and primary works of K.H.D. The findings reveal three major challenges in the digital era: insufficient techno-pedagogical competence, moral erosion, and infrastructural inequality. The ideas of K.H.D. remain relevant in integrating humanistic values with technological advancement. These findings underscore the need to reconstruct the role of educators as morally grounded and digitally competent agents. The implications of this study propose an integrative conceptual model that combines digital competencies with the educational values of K.H.D. as a strategy to strengthen character development and improve the quality of learning in the digital era.